Spontaneous splenic rupture during dengue fever - Sadaf Zafarullah,; Mujahid, Noor Ul Ain; Waheed, Rehman; Mohammad Sohail Asghar,; Afzal, Ameer; Anwar, Jamal (Journal of the Pakistan Medical Association, 2023)
Dengue fever is one of the most frequent arboviral diseases in the world. Dengue is known to cause myocarditis, hepatitis, and neurological illustrations but one of the established presentations is leakage of plasma resulting in circulatory failure. Spontaneous rupture of the spleen is one of the most infrequent but known outcome of dengue fever which has been reported from time to time in literature. We present, here, the case of a 50-year-old patient who developed this condition during dengue fever and was managed in our department successfully. This complication must be kept in mind while treating any case of dengue fever so that it can be avoided or if not then treated timely. Keywords: Spontaneous splenic rupture, Dengue Fever, Dengue haemorrhagic fever, Haemoperitoneum.